2014
DOI: 10.1039/c3tc32378a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the reduction and energy transfer between Eu2+ and Eu3+ in Eu-doped CaAl2Si2O8 materials prepared in air

Abstract: CaAl2Si2O8: Eu material prepared under an air atmosphere shows coexistence of two different valence states of Eu as evidenced by the different emitting color (pink and white-bluish).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 35 publications
3
34
1
Order By: Relevance
“…For the glass-ceramics sample GC48, the broad emission band (FWHM¼ 3003 cm À 1 ) of Eu 2 þ was located at 545 nm which is close to the emission wavelength of melilite Ca 2 Al 2 SiO 7 : Eu 2 þ as reported in previous studies [37]. For Eu 2 þ doped anorthite CaAl 2 Si 2 O 8 [38], the broad emission band was located between 420 nm and 475 nm which is far from the band emission of Eu 2 þ in the GC48 sample. The decrease of the FWHM and the blue-shift of the Eu 2 þ emission band are due to the change in the crystal field through the crystallization process.…”
Section: Photoluminescencementioning
confidence: 72%
“…For the glass-ceramics sample GC48, the broad emission band (FWHM¼ 3003 cm À 1 ) of Eu 2 þ was located at 545 nm which is close to the emission wavelength of melilite Ca 2 Al 2 SiO 7 : Eu 2 þ as reported in previous studies [37]. For Eu 2 þ doped anorthite CaAl 2 Si 2 O 8 [38], the broad emission band was located between 420 nm and 475 nm which is far from the band emission of Eu 2 þ in the GC48 sample. The decrease of the FWHM and the blue-shift of the Eu 2 þ emission band are due to the change in the crystal field through the crystallization process.…”
Section: Photoluminescencementioning
confidence: 72%
“…(We suggest that it is not from the charge transfer band (CTB) according to the excitation spectra monitoring the meission at 620 nm in Figure .) The similiar research results were also reported in the previous reference . In the emission spectra, for CS0, SS0 and BS0, a broad band emission is observed, which locates at 446.6 (CS0), 516.8 (SS0) and 498.8 nm (BS0), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The similiar research results were also reported in the previous reference. [35] In the emission spectra, for CS0, SS0 and BS0, a broad band emission is observed, which locates at 446.6 (CS0), 516.8 (SS0) and 498.8 nm (BS0), respectively. Because f-d transitions appear broad band emission general ranging from 400 to 600 nm in different hosts, [37] the broad band emission can be attributed to the typical 4f 6 5d 1 -4f 7 transition of Eu 2+ .…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that for the reduction process the electron is transferred from the host lattice to the rare earth element. 24,25,29 In our case the azo-pyridine group donates the electron to Eu 3+ and the Eu 3+ cation reduces to Eu 2+ through complexation with the azo-pyridine graphene oxide composite (Scheme 1).…”
mentioning
confidence: 95%